2018
DOI: 10.1093/gerona/gly129
|View full text |Cite
|
Sign up to set email alerts
|

Strong Relation Between Muscle Mass Determined by D3-creatine Dilution, Physical Performance, and Incidence of Falls and Mobility Limitations in a Prospective Cohort of Older Men

Abstract: Unlike DXA lean mass, low D3Cr muscle mass/body mass is strongly related to physical performance, mobility and incident injurious falls in older me.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
172
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(180 citation statements)
references
References 39 publications
4
172
4
Order By: Relevance
“…The D 3 ‐creatine (D 3 Cr) dilution method is a direct assessment of muscle mass . We found that low D 3 Cr muscle mass is strongly related to poor physical performance and subsequent falls and mobility problems in older men, but these relationships were not observed using DXA measures of lean body mass .…”
Section: Introductionmentioning
confidence: 90%
“…The D 3 ‐creatine (D 3 Cr) dilution method is a direct assessment of muscle mass . We found that low D 3 Cr muscle mass is strongly related to poor physical performance and subsequent falls and mobility problems in older men, but these relationships were not observed using DXA measures of lean body mass .…”
Section: Introductionmentioning
confidence: 90%
“…While each component of body composition varies by age, sex, and medical condition, muscle mass is about 50% of lean mass. The non‐muscle components of lean mass is termed residual lean mass …”
Section: Lean Body Mass (Also Referred To As Fat Free Mass)mentioning
confidence: 99%
“…Newly published data from the ongoing MrOS study demonstrate that in older men, those with the lowest muscle mass/weight by D 3 ‐Cr dilution have the highest risk of incident mobility limitation and injurious falls, and much worse physical performance and lower strength than those with higher muscle mass. These associations were not explained by confounding factors such as age, co‐morbidities, or activity level.…”
Section: Lean Body Mass (Also Referred To As Fat Free Mass)mentioning
confidence: 99%
See 1 more Smart Citation
“…Practically, there seems little point in spending up to 10 minutes acquiring a DXA whole body scan in addition to a 30 second hip assessment, when it will add no additional risk information. Other modalities of muscle assessment, such as peripheral quantitative computed tomography,[16] or labeled creatine dilution,[17] might contribute to prediction of fracture independently of DXA BMD, and investigations of the value of these indices in large cohorts, considering also DXA BMD and FRAX probability, are warranted.…”
Section: Editorialmentioning
confidence: 99%